2020
DOI: 10.1177/0300060520964011
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin may inhibit cervical cancer cell proliferation via downregulation of HIST1H3D

Abstract: Objective To investigate the role of fucoxanthin, reported to have significant anticancer effects, and histone Cluster 1 H3 Family Member D (HIST1H3D; implicated in tumorigenesis) in cervical cancer. Methods The half maximal inhibitory concentration (IC50) of fucoxanthin against HeLa and SiHa cervical cancer cells was determined. Differentially expressed genes (DEGs) in SiHa cells treated with IC50 fucoxanthin were screened by high-throughput techniques and subjected to signal enrichment. Following identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Fucoxanthin also effectively suppressed the cell proliferation and colony formation in cervical cancer cells in molecular mechanisms of inducing apoptosis and decreasing the expression of histone cluster 1 H3 family member D (HIST1H3D) [ 56 ]. Murase et al [ 57 ] reported the anti-tumor effects of fucoxanthin in c57bl/6j mice with decreased expressions of the chemokine (C-C motif) ligand 21 (CCL21)/chemokine receptor 7 (CCR7) axis.…”
Section: Resultsmentioning
confidence: 99%
“…Fucoxanthin also effectively suppressed the cell proliferation and colony formation in cervical cancer cells in molecular mechanisms of inducing apoptosis and decreasing the expression of histone cluster 1 H3 family member D (HIST1H3D) [ 56 ]. Murase et al [ 57 ] reported the anti-tumor effects of fucoxanthin in c57bl/6j mice with decreased expressions of the chemokine (C-C motif) ligand 21 (CCL21)/chemokine receptor 7 (CCR7) axis.…”
Section: Resultsmentioning
confidence: 99%
“…There are many pharmacological evidence about its health-promoting effects including anti-cancer 13 and anti-inflammatory properties, 14 its protective effects against doxorubicin-induced cardiotoxicity, 15 Pharmaceutical Sciences (Indexed in ISI and Scopus) https://ps.tbzmed.ac.ir/ diabetic nephropathy, 16 alcoholic liver injury 17 and other metabolic disease. The multi-potent health effects of fucoxanthin are attributed to its unique chemical structure including an allenic bond, an acetyl group, a conjugated carbonyl group, and 5,6-monoepoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 32 facilitated apoptosis and downregulated MMP gene expression in tongue cancer cell lines (CAL-27) [ 194 ]. Additionally, it demonstrated antiproliferative properties against CAL-27 cell lines through alteration of glucose uptake and inactivation of protein kinase B/mammalian target of the rapamycin (Akt/mTOR) signaling pathway [ 195 ]. Moreover, compound 32 could promote cervical cancer cell (HeLa and SiHa) proliferation by suppressing histone Cluster 1 H3 Family Member D (HIST1H3D) expression and arresting the G0/G1 cell cycle [ 195 ].…”
Section: Marine Algaementioning
confidence: 99%